2017
DOI: 10.1073/pnas.1618693114
|View full text |Cite
|
Sign up to set email alerts
|

Classroom sound can be used to classify teaching practices in college science courses

Abstract: Active-learning pedagogies have been repeatedly demonstrated to produce superior learning gains with large effect sizes compared with lecture-based pedagogies. Shifting large numbers of college science, technology, engineering, and mathematics (STEM) faculty to include any active learning in their teaching may retain and more effectively educate far more students than having a few faculty completely transform their teaching, but the extent to which STEM faculty are changing their teaching methods is unclear. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
62
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 19 publications
0
62
0
Order By: Relevance
“…In the second follow-up program, Talk Matters, faculty, in collaboration with postdoctoral fellows, collected direct evidence of teaching innovations by audio-recording all class sessions in one or more of their own courses. Transcripts and audio levels of the recordings were analyzed, and the results are being disseminated in conferences and peer-reviewed publications, with all participating faculty as coauthors ( Owens et al. , 2017 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the second follow-up program, Talk Matters, faculty, in collaboration with postdoctoral fellows, collected direct evidence of teaching innovations by audio-recording all class sessions in one or more of their own courses. Transcripts and audio levels of the recordings were analyzed, and the results are being disseminated in conferences and peer-reviewed publications, with all participating faculty as coauthors ( Owens et al. , 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…To obtain an objective estimate of the amount of active learning in the classes of Biology FEST alumni, we used the Decibel Analysis for Research in Teaching (DART) tool, which is a machine-learning-based tool that can quickly analyze classroom audio recordings with near 90% accuracy ( Owens et al. , 2017 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Just as certain topics may be more or less challenging for undergraduate students to learn, certain pedagogies are more or less effective in promoting learning in the undergraduate science classroom. Although lecture‐only pedagogies have been shown to be relatively ineffective for student learning, many college STEM instructors still use a lecture‐only approach in their teaching . Numerous studies in the STEM education research literature have demonstrated that active‐engagement learning strategies result in higher learning gains and reduce the chance of failure compared with lecture‐only approaches .…”
Section: Introductionmentioning
confidence: 99%
“…In order to properly classify classroom audio into different categories, most previous classroom audio classification methods applied supervised machine learning. Owens et al [8] developed a supervised machine learning method to distinguish between different class conduct modes such as single voice, multiple voices and no voice. Anusha et al [9] used the LIUM speaker diarization toolkit and manually acquired ground-truth labels to automatically classify teacher's speech, children speech and their overlap with 77.3%, 71.6%, and 3.1% accuracies, respectively.…”
Section: Introductionmentioning
confidence: 99%